A “love match” score to compare root exudate attraction and feeding of the plant growth-promoting rhizobacteria Bacillus subtilis, Pseudomonas fluorescens, and Azospirillum brasilense - Fourneau, Eulalie; Pannier, Mélissa; Riah, Wassila; Personeni, Emmanuelle; Morvan-Bertrand, Annette; Bodilis, Josselin; Pawlak, Barbara (Frontiers in Microbiology, 2024)
The rhizosphere is the zone of soil surrounding plant roots that is directly influenced by root exudates released by the plant, which select soil microorganisms. The resulting rhizosphere microbiota plays a key role in plant health and development by enhancing its nutrition or immune response and protecting it from biotic or abiotic stresses. In particular, plant growth-promoting rhizobacteria (PGPR) are beneficial members of this microbiota that represent a great hope for agroecology, since they could be used as bioinoculants for sustainable crop production. Therefore, it is necessary to decipher the molecular dialogue occurring between roots and PGPR in order to promote the establishment of bioinoculants in the rhizosphere, which is required for their beneficial functions. Here, the ability of root exudates from rapeseed (Brassica napus), pea (Pisum sativum), and ryegrass (Lolium perenne) to attract and feed three PGPR (Bacillus subtilis, Pseudomonas fluorescens and Azospirillum brasilense) was measured and compared, as these responses are directly involved in the establishment of the rhizosphere microbiota. Our results showed that root exudates differentially attracted and fed the three PGPR. For all beneficial bacteria, rapeseed exudates were the most attractive and induced the fastest growth, while pea exudates allowed the highest biomass production. The performance of ryegrass exudates was generally lower, and variable responses were observed between bacteria. In addition, P. fluorescens and A. brasilense appeared to respond more efficiently to root exudates than B. subtilis. Finally, we proposed to evaluate the compatibility of each plant-PGPR couple by assigning them a 6,669 words; 4 figures; 3 tables "love match" score, which reflects the ability of root exudates to enhance bacterial rhizocompetence. Taken together, our results provide new insights into the specific selection of PGPR by the plant through their root exudates, and may help to select the most effective exudates to promote bioinoculant establishment in the rhizosphere.